2011
DOI: 10.1017/s095026881100094x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phylogenetic analysis of Greek measles 2010 strains

Abstract: Although elimination of measles virus (MV) by 2010 was a revised target, a new epidemic has been ongoing in Greece and other European countries. The purpose of this study was the molecular and phylogenetic analysis of the Greek MV circulating strain. Twenty-four MV strains isolated from clinical samples during the 2010 outbreak were genotyped and studied in terms of nucleotide variation and phylogeny. All of the detected viruses were of the D4 genotype, which is circulating in Greece in the Roma population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
“…21 reports discussing measles outbreaks were included, reporting on 24 distinct outbreaks and one report that presented all outbreak-related cases in asylum seekers in Germany from 2004 to 2014. Seven reports originated from Germany (16, 24, 29, 37, 52, 56, 59), four from Greece (50, 51, 54, 55), three from Italy (46, 47, 58), two from Spain (45, 48) and one each from Croatia (53), France (26), Ireland (49), Norway (57) and Poland (35). A large proportion of outbreaks were associated with Eastern European migrants, particularly of Roma nationality, including nine outbreaks with an Eastern European index case (16, 37, 46, 47, 51, 52, 58, 62, 67, 68).…”
Section: Resultsmentioning
confidence: 99%
“…In Greece, between 1990 and 2000, 12,250 measles cases were reported; since 2000, two outbreaks occurred in the country, in 2005–2006 and in 2010–2011, with 636 and 189 laboratory-confirmed cases, respectively. Phylogenetic analyses showed that the co-circulation of D4 and D6 genotypes was responsible for the 2005–2006 outbreak [ 6 ], whereas the 2010–2011 outbreak was due to the D4 genotype [ 7 ]. In both outbreaks, the social groups mainly affected were Roma–Greek children and young adults of Greek citizenship.…”
Section: Introductionmentioning
confidence: 99%
“…21 There had been no reported cases of measles G3 in Europe since 2006 until by the end of 2010 it reappeared in several different countries in Europe. 22 Unlike other outbreaks, 11,12,23 six different genotypes have been isolated in Catalonia during the study period, showing several importations as a result of the high incidence in other neighboring territories.…”
Section: Resultsmentioning
confidence: 84%